2013
DOI: 10.3329/agric.v11i1.15246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen on the Growth and Yield of Carrot (Daucus carota L.)

Abstract: An experiment was carried out at farmer's field in Debigonj, Panchagorh during November 2009 to February 2010 to evaluate the effect of four levels of applied nitrogen on the growth and yield of carrot. The experiment was laid out in a Randomized Complete Block Design with three replications. The maximum plant height (47.36 cm), root length (16.17 cm), fresh weight of leaves (145.1 g), dry matter content (11.66 g) of leaves, fresh weight of root (68.33 g), dry matter content of root (15.90%), gross yield (22.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 5 publications
7
20
0
4
Order By: Relevance
“…The maximum root yield (13.46 ± 0.64 t/ha) was obtained from X2 while the minimum (1.17 ± 0.23 t/ha) was obtained from control. Our results obtained on root yield are in conformity with data found in literature: [34]; [13] and [11] also reported similar results in carrot. In this study, root yield (1.17 ± 0.23 t/ha) of carrot from control is lower than those found in literature.…”
Section: ))supporting
confidence: 83%
See 4 more Smart Citations
“…The maximum root yield (13.46 ± 0.64 t/ha) was obtained from X2 while the minimum (1.17 ± 0.23 t/ha) was obtained from control. Our results obtained on root yield are in conformity with data found in literature: [34]; [13] and [11] also reported similar results in carrot. In this study, root yield (1.17 ± 0.23 t/ha) of carrot from control is lower than those found in literature.…”
Section: ))supporting
confidence: 83%
“…In fact, these authors had observed that the length of carrot root varies from 15.77 to 19.50 cm. In addition, studies of [13] reported that the length of carrot roots varies from 15.39 to 17.19 cm. There was a positive and significant correlation (r = 0.64; p <0.05) between the length and diameter of carrot roots obtained in this study.…”
Section: ))mentioning
confidence: 99%
See 3 more Smart Citations